Crisis management process of intensive care nurse managers during the COVID-19 pandemic: a descriptive qualitative study - Şenay Takmak; Ayşe Deliktaş Demirci; Yeliz Karaçar (BMC Nursing)
Abstract Background The COVID-19 pandemic has led to a global health crisis that has deeply affected the healthcare systems. Although numerous studies have focused on the experiences of frontline healthcare workers, there remains a gap in the understanding of how nurse managers in intensive care units (ICUs) navigate this crisis. This study aims to explore the crisis management processes of ICU nurse managers during the pandemic. Methods This study used a qualitative descriptive approach. Using purposive sampling, 14 nurses who served as ICU nurse managers during the pandemic were recruited from public hospitals across Antalya, Türkiye. Semi-structured interviews were conducted between January and June 2022. The data were analysed using thematic analysis. Manual coding was independently conducted by two researchers to enhance the reliability. Findings Thematic analysis identified three main themes and nine subthemes. The first theme, “burdens carried on shoulders”, encompassed nurse managers’ experiences of being advocates for care, compensating for the shortcomings of the system, and bearing the emotional and professional traces of being at the last stop in the care chain. The second theme, “being a facilitator as a manager during the crisis”, reflected their efforts to lead through a collaborative team approach, showed sensitivity to staff and patient needs, and managed the chaos and uncertainty of the pandemic environment. The third theme, “needs to be empowered for the future”, emphasized structural and professional expectations, including the optimization of the nursing profession, increased visibility of nurse managers, and the necessity of considering global dynamics in healthcare systems. Conclusions The experiences of intensive care nurse managers provide a comprehensive framework for understanding investments such as optimizations in the profession and visibility to prepare nurses for future crises. The leadership of intensive care nurse managers should be strengthened, and their requirements should be considered in future crises. Investments should be made in leadership models that are competency-oriented to ensure nurse satisfaction and motivation for intensive care nurse managers. Clinical trial number Not applicable.